Analysis of Cholesterol Content, E. Coli Bacteria, and Organoleptic Value of Rarang Chicken Cooking Based on Slaughter Age - Alfian G. M, Aji; Bulkaini, Bulkaini; Kisworo, Djoko; Ichsan, Ichsan; Rosyidi, A.; Yuliani, Enny; Permatasari, Lina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Rarang chicken dish is a very special dish with a unique taste on Lombok Island. This research aims to determine the effect of slaughter age on cholesterol content, E.Coli and organoleptic value of Rarang chicken dishes. The materials used were 15 male chickens and a number of Rarang chicken cooking spices. The method used is an experimental method in the Animal Product Processing Technology Laboratory, Faculty of Animal Science, University of Mataram, which is designed based on a Completely Randomized Design in a one-way pattern with 3 treatments and 5 replications: namely P1 = 6 weeks of slaughter age, P1 = 7 weeks of slaughter age and P2 = 8 weeks of slaughter age. Research data such as cholesterol content, E.Coli and organoleptic values ​​were analyzed using analysis of variance followed by the Tukkey Honestly Different Test. The results of the research showed that the cholesterol content, E. Coli, and organoleptic value of Rarang chicken dishes based on age at slaughter were respectively: total cholesterol ranges from 32.18-45.30%; E.Coli content of 0.4 CFU/g, with organoleptic values ​​(color, aroma, taste and tenderness) accepted by consumers. Conclusion: Super village chicken which is processed into Rarang chicken dishes at 7 weeks of slaughter age can provide relatively low total cholesterol and E.Coli content, with organoleptic values (color and aroma) that consumers like, the taste is relatively delicious and Rarang chicken dishes are relatively tender.